The Long-Term Study of Urinary Biomarkers of Renal Injury in Spontaneously Hypertensive Rats - Sebastián Montoro-Molina; Andrés Quesada; Francisco O'Valle; Natividad Martín Morales; María del Carmen de Gracia; Isabel Rodríguez-Gómez; Antonio Osuna; Rosemary Wangensteen; Félix Vargas (Karger Publishers, 2021)
Background: The age-related increase in blood pressure in spontaneously hypertensive rats (SHRs) is associated to cardiac hypertrophy, heart failure, and renal injury. Here, we investigated for the first time the urinary enzymatic activities of glutamil aminopeptidase (GluAp), alanyl aminopeptidase (AlaAp), dipeptidyl peptidase-4 (DPP4), and Klotho urinary levels, proteins that are strongly expressed in the kidney, as early biomarkers of renal injury in SHRs. Methods: Male SHR and Wistar Kyoto (WKY) rats were studied from 2 to 8 months old. Systolic blood pressure (SBP), the heart rate (HR), metabolic variables, and urinary markers were measured monthly. At the end of the study, a histopathological evaluation of the kidney was performed. Results: Kidneys of SHR did not develop signs of relevant histopathological changes, but showed increased glomerular area and cellularity. Plasma creatinine was decreased, and creatinine clearance was augmented in SHR at the end of the study. Urinary excretion of Klotho was higher in SHR at 5 and 8 months old, whereas plasma Klotho levels were similar to WKY. GluAp, AlaAp, and DPP4 urinary activities were increased in SHR throughout the time-course study. A positive correlation between glomerular area and cellularity with creatinine clearance was observed. Urinary GluAp, AlaAp, DPP4, and Klotho showed positive correlations with SBP. Conclusions: GluAp, AlaAp, DPP4, and Klotho in the urine are useful tools for the evaluation of renal damage at early stages, before the whole histopathological and biochemical manifestations of renal disease are established. Moreover, these observations may represent a novel and noninvasive diagnostic approach to assess the evolution of kidney function in hypertension and other chronic diseases.